The Effect of Production Costs and Marketing Costs on Net Income in FnB Sector Manufacturing - Rustam, Andi; Hasni, Rusni (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study examines the effect of production and marketing costs on net income in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. It uses quantitative research and purposive sampling. Sixteen company samples were selected from 148 companies. The data analysis technique in this study used multiple linear regression. This research data processing uses SPSS 22, 2024. The results of this study partially affect production costs on net profit, and marketing costs do not affect net profit.